THE DEVELOPMENT AND MODERNIZATION OF THE UZBEK LANGUAGE - Sunatillayeva , Ezoza (Scientific practical conference, 2026)
The article explores the development and modernization of the Uzbek language as a symbol of national identity and independence. It analyzes state policy, the role of education, and digital transformation, emphasizing the need to preserve the cultural spirit of the language while adapting it to modern scientific and technological demands.